A 2000-year documentary record of levee breaches on the lower Yellow River and their relationship with climate changes and human activities. (March 2021) - Li, Wen-Jia; Yu, Shi-Yong; Pan, Jianrong; Cao, Xianyong; Chen, Yingying; Wang, Yi
The Yellow River floodplain represents a fertile landmass that contributes significantly to human welfare and thus has been colloquially known as the birthplace of Chinese civilization. The sediment-laden nature of the Yellow River gave rise to a super-elevated channel belt, which is prone to failure particularly in the summer months when excessive precipitation occurs, resulting in cataclysmic floods traditionally regarded as "China's Sorrow." Therefore, a deeper understanding of levee breach frequency in this area is especially important for the assessment of socio-economic risk of levee breaches associated with future climate changes. To better understand the nature, evolution, and driving mechanisms of levee breaches on the lower Yellow River, it is necessary to place the instrumental data within a longer time framework. Here, we retrieve past information about levee breaches on the lower Yellow River since AD 11 from various documentary sources such as official histories of China. We evaluated each line of descriptions and narratives about the location, timing, and nature of each event in these documents, ending up with a detailed timeline of levee breaches on the lower Yellow River during the last 2000 years on an annual time scale. Our results reveal remarkable variations in the frequency of levee breaches superimposed on a long-term increasing trend. In addition to climate changes, the iterative embankment-siltation-breaching process caused a feedback: more breaches result in much more channel siltation, which in turn leads to even more breaches. The enhanced farming in the Loess Plateau played a pivotal role in the formation and operation of this positive feedback. Our findings may not only help improve the assessment of socio-economic risk of levee breaches associated with future climate changes, but also provide consulting information for hydraulic engineering and infrastructural designs in the lower Yellow river area.